Empowering mesenchymal stem cells for ocular degenerative disorders - Ding, Shirley Suet Lee; Subbiah, Suresh Kumar; Khan, Mohammed Safwan Ali; Farhana, Aisha; Mok, Pooi Ling (MDPI, 2019)
Multipotent mesenchymal stem cells (MSCs) have been employed in numerous pre-clinical and clinical settings for various diseases. MSCs have been used in treating degenerative disorders pertaining to the eye, for example, age-related macular degeneration, glaucoma, retinitis pigmentosa, diabetic retinopathy, and optic neuritis. Despite the known therapeutic role and mechanisms of MSCs, low cell precision towards the targeted area and cell survivability at tissue needing repair often resulted in a disparity in therapeutic outcomes. In this review, we will discuss the current and feasible strategy options to enhance treatment outcomes with MSC therapy. We will review the application of various types of biomaterials and advances in nanotechnology, which have been employed on MSCs to augment cellular function and differentiation for improving treatment of visual functions. In addition, several modes of gene delivery into MSCs and the types of associated therapeutic genes that are important for modulation of ocular tissue function and repair will be highlighted.